2022
DOI: 10.1021/acs.est.1c08883
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Insights into Activation of Peroxides by Quinones: Formation of Oxygen-Centered Radicals or Singlet Oxygen

Abstract: In this work, the mechanism of the activation of peroxides by quinones has been investigated through quantum chemical calculations. Hydrogen peroxide (H 2 O 2 ), peroxomonosulfate (PMS), peracetic acid (PAA), and CH 3 OOH were chosen as the model peroxides and p-benzoquinone (p-BQ) and tetrachloro-1,4-benzoquinone (TCBQ) as the model quinones. The nucleophilic attack of peroxides can occur on the carbonyl and olefinic carbons of quinones. For p-BQ, the nucleophilic attack of HO 2 − , CH 3 OO − , PMS, and PAA m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 34 publications
2
12
0
Order By: Relevance
“…Alternately, SO 4 •– / • OH radicals were previously reported to convert oxygen moieties present in humic constituents into SQ •– species, which are capable of degrading antibiotics and phenolic compounds, with mild second-order reaction rate constants in the range of 10 4 to 10 6 M –1 s –1 . , Interestingly, reminiscent of the above EPR outcomes (Figure c), a huge upsurge in the signal intensity for the TEMP– 1 O 2 adduct was recorded with HA dosages ranging from 20 to 500 mg (Figure b). Recent studies have found that persulfate could induce the nucleophilic attack on the carbonyl carbons of quinones to release 1 O 2 . We therefore speculate that quinone moieties may be involved in the formation of 1 O 2 .…”
Section: Resultssupporting
confidence: 91%
“…Alternately, SO 4 •– / • OH radicals were previously reported to convert oxygen moieties present in humic constituents into SQ •– species, which are capable of degrading antibiotics and phenolic compounds, with mild second-order reaction rate constants in the range of 10 4 to 10 6 M –1 s –1 . , Interestingly, reminiscent of the above EPR outcomes (Figure c), a huge upsurge in the signal intensity for the TEMP– 1 O 2 adduct was recorded with HA dosages ranging from 20 to 500 mg (Figure b). Recent studies have found that persulfate could induce the nucleophilic attack on the carbonyl carbons of quinones to release 1 O 2 . We therefore speculate that quinone moieties may be involved in the formation of 1 O 2 .…”
Section: Resultssupporting
confidence: 91%
“…This indicated that the loading of AQPDA on the CNT generated ROS through a sequence of reactions involving the breakdown of essential intermediates, displacement, and nucleophilic addition to PMS, thereby greatly increasing SMX degradation. Similar phenomena were previously described. ,, …”
Section: Resultssupporting
confidence: 90%
“…While 1 O 2 production was confirmed in this system with FFA ([ 1 O 2 ] ss = 2 pM) and may have contributed to the degradation of 6PPDQ, it is apparent that there is a second unknown reaction contributing to 6PPDQ attenuation in these microcosms. Previous work has reported that semiquinones, produced by the one-electron reduction of quinones, may catalyze metal-independent reduction of hydrogen peroxide to generate a hydroxyl radical. While this work focuses on photochemical pathways, future work should investigate the potential interplay between 6PPDQ redox properties and environmental photoproduction of hydrogen peroxide . To further test the hypothesis that the production of 1 O 2 in sunlit waters by dissolved organic matter may contribute to its degradation in the environment, we conducted additional experiments employing either furfuryl alcohol (FFA, 5 mM) or sodium azide (NaN 3 , 1 mM) as a 1 O 2 scavenger in SRFA microcosms.…”
Section: Resultsmentioning
confidence: 99%